The learning organization : developing democracy at work - Garratt, Bob (HarperCollinsBusiness, Profile Books, 2000)
"In this fully revised edition of his book, Bob Garratt, one of the world's leading experts in management education, offers a fresh perspective on the way organizations work. In the knowledge economy people are the key to organizational learning and need to be much more involved in the critical debate within organizations. The very nature of relationships between employers and employees, owners and their agents, needs to be re-evaluated." "As well as considering the work of other business writers, Garratt employs a wide range of experimental models and graphic illustrations to clearly demonstrate his theories. This exciting and informative book is a challenge to all directors, management educators and the business community at large."--BOOK JACKET.